1989
DOI: 10.1021/ja00200a058
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangement approach to bridgehead substitution of 1-methoxybicyclo[2.2.2]oct-5-en-2-ones

Abstract: Bicyclo[2.2.2]oct-5-en-2-ones (1) are potential compounds which are convertible into [5-5] fused-ring systems (2) by the triplet sensitized photochemical process, oxa-di-tr-methane rearrangement,1 and also into [6-6] fused-ring systems (4) via vinylation followed by the oxy-Cope rearrangement of the exoalcohols (3).2 In connection with our studies on rearrangement strategies from bridged polycyclic compounds to [m-ri\ fused-ring

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…Koreeda found that 3-methyl-3-[4-(trimethylsilyl)-3-butynyl]cyclopentyl ( 32a ), generated reductively with Bu 3 SnH, cyclizes to give 65% of bicyclic vinylsilane 33 resulting from the desired 6- exo -cyclization but that radical 32b abstracts a hydrogen from Bu 3 SnH to afford mainly 34 resulting from reduction 8b. The failure of 32b to cyclize provides further evidence of the ring strain in the gymnomitrane ring system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Koreeda found that 3-methyl-3-[4-(trimethylsilyl)-3-butynyl]cyclopentyl ( 32a ), generated reductively with Bu 3 SnH, cyclizes to give 65% of bicyclic vinylsilane 33 resulting from the desired 6- exo -cyclization but that radical 32b abstracts a hydrogen from Bu 3 SnH to afford mainly 34 resulting from reduction 8b. The failure of 32b to cyclize provides further evidence of the ring strain in the gymnomitrane ring system.…”
Section: Resultsmentioning
confidence: 99%
“…Asakawa isolated 9α-hydroxygymnomitryl acetate ( 2 ) and 9-oxogymnomitryl acetate ( 3 ) from the liverwort Plagiochila Trabeculata in 1988 . The unusual tricyclic gymnomitrane ring system attracted much interest, culminating in five different syntheses reported in 1979. Coates 3 and Paquette 4 prepared dione 5 by an aldol reaction of keto aldehyde 4a and oxidation of the resulting alcohol. Addition of methyllithium to 5 and dehydration gave a difficultly separable mixture of gymnomitrone ( 6 ) and isogymnomitrone ( 7 ).…”
mentioning
confidence: 99%
“…Radical cyclizations constitute another popular approach to the construction of the [3.3.3]propellane cores, either via an intramolecular radical cyclization from a cyclopentane or diquinane core bearing appropriate side chains 60,84,[94][95][96][97][98][99][100][101][102] or by means of a domino transannular radical cyclization of a substituted cyclooctane derivative. [103][104][105] 3.5.1 Curran and co-workers.…”
Section: Radical Cyclizationsmentioning
confidence: 99%
“…Uyehara et al's approach to [3.3.3]propellanes 99a and 99b is based on their methodology to introduce substituents at both bridge heads of bicyclo[2.2.2]oct-5-en-2-ones and on a photo-mediated rearrangement of the substituted b,g-unsaturated ketone into tricyclic structures like 172 (Scheme 23). 94,95,116 In this way, all the methyl substituents required for the synthesis of (AE)-modhephene ((AE)-1) are installed prior to the construction of the propellane core. A straightforward radical cyclization of bromide 173 yielded a mixture of propellanes 99a and 99b, which were isolated by using HPLC.…”
Section: Radical Cyclizationsmentioning
confidence: 99%
“…In the second example the synthesis of gymnomitrol is reported (Scheme 4) [7]. In the first step the suitable substrate to be irradiated was obtained through a double alkylation of a ketonic precursor.…”
Section: Diastereoselective Photochemical Re-actionsmentioning
confidence: 99%